Electroacupuncture relieves depression-like symptoms in rats exposed to chronic unpredictable mild stress by activating ERK signaling pathway. (6th March 2017) - Li, Weidong; Zhu, Yan; Saud, Shakir M.; Guo, Qiujun; Xi, Shengyan; Jia, Baohui; Jiao, Shuang; Yang, Xiuyan; Lu, Jun; Song, Sihong; Tu, Ya
Highlights: Chronic Unpredictable Mild Stress (CUMS) induces depression-like symptoms in rats. CUMS increases hippoampal apoptotic rates and decreases Bcl-2 expression. CUMS inhibits ERK signal pathway. Anti-depression effect of EA is mediated by regulation of ERK signal pathway. ERK activation triggers apoptosis mechanism to improve depression symptoms. Abstract: Electroacupuncture (EA) has been shown to alleviate the symptoms associated with major depressive disorder; however, the underlying mechanisms remain unclear. While the mainstay treatment for depression are pharmacological agents that modulate serotonergic and/or noradrenergic activity of the brain, recent data suggest that, neurotrophins may play a larger role in the pathogenesis of depression and may offer better therapeutic potential in alleviating symptoms associated with depression. One downstream target of neurotrophins is the extracellular signal-regulated kinase (ERK)/Mitogen-activated protein kinase (MAPK) cascade, a major mediator of cellular stress often associated with clinical depression. In this study, we assessed whether the efficacy of EA is due to regulation of these novel pathways using an animal model of depression induced by chronic unpredictable mild stress (CUMS). We found that EA stimulation at specific locations, Baihui (GV20), and Yintang (GV29) ameliorated the behavioral responses of CUMS, which included reduced locomotion, decreased sucrose intake and weight loss. Furthermore, EA increased the activation of ERK and ribosomal s6 kinase (RSK) levels under stress. Both the behavioral and biochemical responses to EA were attenuated with administration of ERK inhibitor, suggesting that EA improves depression-like symptoms in stressed rats, in part, by activation of ERK signaling.